An educational software package for electric power system course - Lam Yuen San (Universiti Malaysia Perlis, 2009)
A software package is developed to perform power system analysis such as load flow analysis, fault analysis and impedance calculation. This software package is named as “PSA” which means “Power System Analysis”. It is intended for electric power system students. PSA is developed under MATLAB 7.0 for Microsoft Window application. The notation used in the program is mostly compatible with the format used in electric power system textbooks. Students can see the inner structure of computation function files where the MATLAB codes are simple and easy to study. With PSA, students can use it as a tool to solve the problems in textbooks. PSA can helps students more understand in power system analysis calculation steps and can improve their hand calculation skills.